Time trends in the risk of delayed cerebral ischemia after subarachnoid hemorrhage: a meta-analysis of randomized controlled trials - Rigante, Luigi; Lieshout, Jasper Hans van; Vergouwen, Mervyn D. I.; Griensven, Carlijn H. S. van; Vart, Priya; Loo, Lars van der; Vries, Joost de; Vinke, Ruben Saman; Etminan, Nima; Aquarius, Rene; Gruber, Andreas; Mocco, J.; et al. (Neurosurgical focus, 2022)
OBJECTIVE Delayed cerebral ischemia (DCI) contributes to morbidity and mortality after aneurysmal subarachnoid hemorrhage (aSAH). Continuous improvement in the management of these patients, such as neurocritical care and aneurysm repair, may decrease the prevalence of DCI. In this study, the authors aimed to investigate potential time trends in the prevalence of DCI in clinical studies of DCI within the last 20 years. METHODS PubMed, Embase, and the Cochrane library were searched from 2000 to 2020. Randomized controlled trials that reported clinical (and radiological) DCI in patients with aSAH who were randomized to a control group receiving standard care were included. DCI prevalence was estimated by means of random-effects meta-analysis, and subgroup analyses were performed for the DCI sum score, Fisher grade, clinical grade on admission, and aneurysm treatment method. Time trends were evaluated by meta-regression. RESULTS The search strategy yielded 5931 records, of which 58 randomized controlled trials were included. A total of 4424 patients in the control arm were included. The overall prevalence of DCI was 0.29 (95% CI 0.26-0.32). The event rate for prevalence of DCI among the high-quality studies was 0.30 (95% CI 0.25-0.34) and did not decrease over time (0.25% decline per year; 95% CI −2.49% to 1.99%, p = 0.819). DCI prevalence was higher in studies that included only higher clinical or Fisher grades, and in studies that included only clipping as the treatment modality. CONCLUSIONS Overall DCI prevalence in patients with aSAH was 0.29 (95% CI 0.26-0.32) and did not decrease over time in the control groups of the included randomized controlled trials.
Gesehen am 30.04.2024